Cadmium mediated phytotoxic impacts in Brassica napus: Managing growth, physiological and oxidative disturbances through combined use of biochar and Enterobacter sp. MN17. (1st July 2020) - Sabir, Asma; Naveed, Muhammad; Bashir, Muhammad Asaad; Hussain, Azhar; Mustafa, Adnan; Zahir, Zahir Ahmad; Kamran, Muhammad; Ditta, Allah; Núñez-Delgado, Avelino; Saeed, Qudsia; Qadeer, Abdul
Abstract: Cadmium (Cd) is a toxic heavy metal with unknown biological role. Interactive effect of Enterobacter sp. MN17 and biochar was studied on the growth, physiology and antioxidant defense system of Brassica napus under Cd contaminated soil. A multi-metal tolerant endophytic bacterium, Enterobacter sp. MN17, was able to grow in tryptic soy agar (TSA) medium with up to 160, 200, 300, 700, 160 and 400 μg mL −1 of Cd, Cu, Cr, Pb, Ni and Zn, respectively. Paper and pulp waste biochar was prepared at 450 °C and applied to pots (7 kg soil) at a rate of 1% ( w/w ), while Cd was spiked at 80 mg kg −1 soil. Application of Enterobacter sp. MN17 and biochar, alone or combined, was found effective in the amelioration of Cd stress. Combined application of Enterobacter sp. MN17 and biochar caused the maximum appraisal in shoot and root length (52.5 and 76.5%), fresh and dry weights of shoot (77.1 and 70.7%) and root (81.2 and 57.9%), photosynthetic and transpiration rate (120.2 and 106.6%), stomatal and sub-stomatal conductance (81.3 and 75.5%), chlorophyll content and relative water content (RWC) (78.4 and 102.9%) than control. Their combined use showed a significant decrease in electrolyte leakage (EL), proline, malondialdehyde (MDA), catalase (CAT), glutathione peroxidase (GPX), glutathione S transferase (GST) and superoxide dismutase (SOD) by 39.3, 39.4, 39.5, 37.0, 39.0 42.1 and 30.8%, respectively, relative to control. Likewise, the combined application of bacterial strain MN17 and biochar reduced Cd in soil by 45.6%, thereby decreasing its uptake in root and shoot by 40.1 and 38.2%, respectively in Cd contaminated soil. The application of biochar supported the maximum colonization of strain MN17 in the rhizosphere soil, root and shoot tissues. These results reflected that inoculation with Enterobacter sp. MN17 could be an effective approach to accelerate biochar-mediated remediation of Cd contaminated soil for sustainable production of crops. Graphical abstract: Image 1 Highlights: Cd contamination inhibited growth, altered physiological and biochemical responses of B. napus . Combined use of Enterobacter sp. MN17 and biochar retrieved harmful effects of Cd in B. napus . Biochar and bacterium together mobilized Cd in soil but reduced Cd uptake by plants. Productivity of Cd-contaminated soils could be enhanced by biochar and strain MN17.